The Strategy of Reform in the Previously Centrally-Planned Economies of Eastern Europe : Lessons and Challenges - Borensztein, Eduardo (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1993)
This paper analyzes some of the lessons that can be drawn from the experience of Eastern Europe in the process of transition to a market economy that is under way, and examines some key challenges currently facing policymakers in these economies. The paper studies the constraints affecting the general strategy of reform--rapid versus gradual--that was adopted, and the output decline initially experienced and its effect on medium-term growth perspectives. The paper also discusses the implementation of mass privatization schemes, and the type and extent of government intervention in the restructuring process. This is a Paper on Policy Analysis and Assessment and the author(s) would welcome any comments on the present text. Citations should refer to a Paper on Policy Analysis and Assessment of the International Monetary Fund, mentioning the authors) and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.